1981
DOI: 10.1113/jphysiol.1981.sp013775
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude‐ and instruction‐dependent modulation of movement‐related electromyogram activity in humans.

Abstract: 2. A 'triphasic' pattern of EMG activity was associated with all movements in this study. All bursts in this pattern were more clearly defined in faster movements whether the increased speed of movement was a result of increased movement amplitude or of the instruction-related 'intent' of the subject.3. The magnitudes of the two agonist EMG bursts showed identical linear dependencies on movement amplitude. The slope of this relation was instructiondependent, being greatest for 'fast' and least for 'accurate' m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
83
3
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(93 citation statements)
references
References 12 publications
6
83
3
1
Order By: Relevance
“…This model emerged from initial studies examining targeted isometric force tracking tasks in cats (Ghez & Vicario, 1978a, 1978b and was later expanded to isometric studies in humans (Gordon & Ghez, 1984, 1987a, 1978b). Brown and Cooke extended this model to single joint movements (Brown & Cooke, 1981a, 1981b, an extension that was further validated by a number of studies Hoffman & Strick, 1986;Mustard & Lee, 1987;Krakauer, Gordon, Veytsman, & Ghez, 2002;. The pulse-step model proposes that rapid limb movements are governed by an initial pulsatile output that determines the amplitude and duration of the initial acceleration impulse.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This model emerged from initial studies examining targeted isometric force tracking tasks in cats (Ghez & Vicario, 1978a, 1978b and was later expanded to isometric studies in humans (Gordon & Ghez, 1984, 1987a, 1978b). Brown and Cooke extended this model to single joint movements (Brown & Cooke, 1981a, 1981b, an extension that was further validated by a number of studies Hoffman & Strick, 1986;Mustard & Lee, 1987;Krakauer, Gordon, Veytsman, & Ghez, 2002;. The pulse-step model proposes that rapid limb movements are governed by an initial pulsatile output that determines the amplitude and duration of the initial acceleration impulse.…”
Section: Introductionmentioning
confidence: 99%
“…Intended distance and velocity are thus thought to be specified by modifications in control pulse amplitude. Brown and Cooke (1981a, 1981b showed that acceleration amplitude is determined by initial agonist burst amplitude, and that both measures are resistant to peripheral sensory events evoked by mechanical perturbations. They concluded that pulse-height control is largely due to preplanning processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electromyographic analysis of rapid (ballistic) goal-directed movements in man disclosed a distinctive triphasic activity pattern in a wide variety of antagonistic muscle pairs (Wacholder 1923;Hufschmidt 1952;Hopf et al 1973;Angel 1974;Hallett and Marsden 1973;Hallett et al 1975;Brown and Cooke 1981;Day and Marsden 1982;. Hallett et al (1975) postulated that the timing of this pattern was constant and that movements of different amplitudes were achieved by varying only the size of the bursts.…”
Section: Introductionmentioning
confidence: 99%
“…Time calibration applies to B, C, F, and G. Individual traces were aligned for averaging to a position trigger signal elicited at 2 ~ increased. The size and the timing of the burst appear to be subtly adjusted to the precise nature of the task by a highly versatile programme (Brown and Cooke 1981;Marsden et al 1983;Meinck et al 1984).…”
Section: Introductionmentioning
confidence: 99%